Chop suey, USA : the story of Chinese food in America - Chen, Yong, 1960- (Arts and traditions of the table., 2014)
American diners began to flock to Chinese restaurants more than a century ago, making Chinese food the first mass-consumed cuisine in the United States. By 1980, it had become the country's most popular ethnic cuisine. Chop Suey, USA offers the first comprehensive interpretation of the rise of Chinese food, revealing the forces that made it ubiquitous in the American gastronomic landscape and turned the country into an empire of consumption.